An eigenstructure assignment approach to FDI for the industrial actuator benchmark test - Jørgensen, R.B.; Patton, R.J.; Chen, J. (Control engineering practice, 1995)
This paper examines the robustness in modelling uncertainties of an observer-based fault-detection and isolation scheme applied to the industrial actuator benchmark problem. A linear dynamic model is used, and the observer is designed using eigenstructure assignment. Fault detection is achieved with a fixed threshold. The design and test example is an electromechanical system, subject to an actuator fault, a sensor fault and a load disturbance. The paper outlines the design, application, and an evaluation of the robustness of the method.